Ferritin Light Chain Confers Protection Against Sepsis-Induced Inflammation and Organ Injury - Zarjou, Abolfazl; Black, Laurence M.; McCullough, Kayla R.; Hull, Travis D.; Esman, Stephanie K.; Boddu, Ravindra; Varambally, Sooryanarayana; Chandrashekar, Darshan S.; Feng, Wenguang; Arosio, Paolo; Poli, Maura; Balla, Jozsef; et al. (Frontiers in Immunology, 2019)
Despite the prevalence and recognition of its detrimental impact, clinical complications of sepsis remain a major challenge. Here, we investigated the effects of myeloid ferritin heavy chain (FtH) in regulating the pathogenic sequelae of sepsis. We demonstrate that deletion of myeloid FtH leads to protection against lipopolysaccharide-induced endotoxemia and cecal ligation and puncture-induced model of sepsis as evidenced by reduced cytokine levels, multi-organ dysfunction and mortality. We identified that such protection is predominantly mediated by the compensatory increase in circulating ferritin (ferritin light chain; FtL) in the absence of myeloid FtH. Our in vitro and in vivo studies indicate that prior exposure to ferritin light chain restrains an otherwise dysregulated response to infection. These findings are mediated by an inhibitory action of FtL on NF-κB activation, a key signaling pathway that is implicated in the pathogenesis of sepsis. We further identified that LPS mediated activation of MAPK pathways, specifically, JNK and ERK were also reduced with FtL pre-treatment. Taken together, our findings elucidate a crucial immunomodulatory function for circulating ferritin that challenges the traditional view of this protein as a mere marker of body iron stores. Accordingly, these findings will stimulate investigations to the adaptive nature of this protein in diverse clinical settings.